1994
DOI: 10.1111/j.1530-0277.1994.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Tridimensional Personality Hypothesis of Alcoholism Using Empirically Multivariate Typology

Abstract: Cloninger (1987) has hypothesized a tridimensional personality theory for two types of alcoholism, type 1 and type 2, that exhibit opposing clinical characteristics and personality traits. The Tridimensional Personality Questionnaire (TPQ) is designed to test this hypothesis on three independent dimensions--novelty seeking (NS), harm avoidance (HA), and reward dependence (RD)--to evaluate the personality trait. We examined the tridimensional personality hypothesis by comparing TPQ scores between two empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…Finally, we also note that some studies failed to replicate the binary models (Yoshino et al 1994;Sannibale and Hall 1998). Furthermore, Epstein and colleagues (2002) suggested that the Cloninger model is redundant with the age of onset schema and conclude that the dichotomous typologies may not be complex enough to be clinically useful descriptors of alcoholic samples (Epstein et al 2002).…”
Section: Binary Modelsmentioning
confidence: 89%
“…Finally, we also note that some studies failed to replicate the binary models (Yoshino et al 1994;Sannibale and Hall 1998). Furthermore, Epstein and colleagues (2002) suggested that the Cloninger model is redundant with the age of onset schema and conclude that the dichotomous typologies may not be complex enough to be clinically useful descriptors of alcoholic samples (Epstein et al 2002).…”
Section: Binary Modelsmentioning
confidence: 89%
“…Early-onset alcohol abuse is predicted by undercontrolled behavior at age 3 years (Caspi et al, 1996), high novelty-seeking and low harm avoidance in childhood (Cloninger et al, 1988;Masse and Tremblay, 1997) and adolescence (Wills et al, 1994), and externalizing (conduct problems) symptoms in early adolescence (Chassin et al, 1999). Early-onset antisocial (type II/B) alcoholism has been associated with disinhibited personality traits such as impulsivity, boredom susceptibility, thrill-and adventure-seeking (Sullivan et al, 1990;von Knorring et al, 1985von Knorring et al, , 1987, novelty-seeking (Ball, 1996;Ball et al, 1998;Sullivan et al, 1990;Yoshino et al, 1994), and aggressiveness (Babor et al, 1992;von Knorring et al, 1987). Although observational studies of children clearly implicate low harm avoidance in the development of substance use (Cloninger et al, 1988;Masse and Tremblay, 1997), low harm avoidance is not consistently reported in questionnaire studies of antisocial EOA (Ball et al, 1998;Sullivan et al, 1990;Yoshino et al, 1994).…”
Section: Studymentioning
confidence: 97%
“…Previous studies had reported that younger and early-onset alcoholics differ from late-onset and middle-aged alcoholics in terms of antisocial personality disorder, impulsiveness, and poor prognosis (Babor et al, 1992;Cloninger, 1987;Yoshino et al, 1994). The present study's finding that both young and middle-aged alcoholics have OCPD traits is consistent with the findings of the ECA studies (Karno et al, 1988;Regier et al, 1990), which reported the coprevalence of OCD and various disorders, including alcoholism, and with a study of inpatient alcoholics (Hesselbrock et al, 1985), which reported the coprevalence of alcoholism and various anxiety disorders, including OCD.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies (Babor et al, 1992;Cloninger, 1987;Yoshino et al, 1994) have noted that young and early-onset alcoholics differ from late-onset alcoholics in a variety of clinical characteristics, including personality traits. If younger and early-onset alcoholics have a higher coprevalence of OCD symptoms than late-onset alcoholics, as suggested by the ECA study, their OCD traits may relate to an increased number of compulsive symptoms and behaviors.…”
mentioning
confidence: 97%